DEVELOPMENT AND INVESTIGATION OF RECIPROCATING SCREW WITH FLEXIBLE HELICAL SURFACE - Hevko, R.B; Zalutsky, S.Z.; Tkachenko, I.G.; Klendiy, O.M. (INMATEH - Agricultural Engineering, 2015)
The analysis of known reciprocating screw working parts with flexible helical surfaces and screw conveyer operation has been carried out. A new structure of reciprocating screw with flexible helical surface and its manufacturing method have been proposed. The bench has been developed and manufactured for conduction of experimental researches. Experimental findings have been provided considering the definition of influence on the value of flexible sheet deformation, its width and cantilevered cog size as well as comparative results of grain material destruction degree with rigid and flexible reciprocating screw working surfaces. Проведено аналіз відомих конструкцій робочих органів шнеків з еластичними поверхнями та процесів роботи гвинтових конвеєрів. Запропоновано нову конструкцію шнека з еластичною гвинтовою поверхнею та спосіб його виготовлення. Розроблено та виготовлено стенд для проведення експериментальних досліджень. Наведено результати експериментальних досліджень з визначення впливу на величину деформації секції еластичної пластини її ширини та величини консольного виступу, а також порівняльні результати ступеня пошкодження зернового матеріалу шнеком із жорсткою та еластичною робочими поверхнями.
РОЗРОБКА ТА ДОСЛІДЖЕННЯ ШНЕКА З ЕЛАСТИЧНОЮ ГВИНТОВОЮ ПОВЕРХНЕЮ
Keywords: reciprocating screw; flexible helical surface; unit of flexible sheet; bench; deformation; sheet width; cantilevered cog size; шнек; еластична гвинтова поверхня; стенд; деформація; ширина пластини; величина консольного виступу